Prescription for excellence [ leadership lessons for creating a world-class customer experience from UCLA Health System - Michelli, Joseph A. , 1960- (McGraw-Hill, 2011)
Provides a business model based on the UCLA Health System and explains how other businesses can use the same system to provide excellent customer experiences and dominate their industry